Garlic: a systematic review of the effects on cardiovascular diseases - IMAIZUMI, Vitor Massami (130, 2022)
Allium sativum (garlic) certainly is one of the oldest horticultural crops in the world and presents bioactive compounds that are related to the garlic’s effects on human health. Several authors have shown beneficial effects on diabetes, hypertension, dyslipidemia, obesity, and cardiovascular diseases (CVD), which are among the most relevant causes of mortality in the world. The aim of this systematic review was to evaluate the effects of garlic in the risk factors of CVD and evaluate its economic importance. MEDLINE–PubMed, COCHRANE, EMBASE, and Google Scholar databases were searched. The included studies showed that the use of garlic can reduce blood pressure, waist circumference, body mass index, LDL-c, non-HDL-c, total cholesterol, triglycerides, and inflammatory markers. It also can increase the levels of HDL-c and can improve cardiovascular parameters such as coronary artery calcium, microcirculation, epicardial and periaortic adipose tissue, post occlusive reactive hyperemia, low attenuation plaque, carotid intima-media thickness; and carotid intima-media thickness. Due to these reasons, garlic can be considered in the prevention and treatment of CVD risk factors.

RESUMO: O Allium sativum (alho) certamente é uma das culturas hortícolas mais antigas do mundo e apresenta compostos bioativos que estão relacionados aos efeitos do alho na saúde humana. Vários autores têm mostrou efeitos benéficos sobre diabetes, hipertensão, dislipidemia, obesidade e doenças cardiovasculares (DCV), que estão entre as mais relevantes causas de mortalidade no mundo. O objetivo disto revisão sistemática foi avaliar os efeitos do alho nos fatores de risco de DCV e avaliar sua importância econômica. MEDLINE–PubMed, COCHRANE, EMBASE e bancos de dados Google Scholar foram pesquisados. Os estudos incluídos mostraram que o uso do alho pode reduzir a pressão arterial, circunferência da cintura, índice de massa corporal, LDL-c, não-HDL-c, colesterol total, triglicerídeos e marcadores inflamatórios. Também pode aumentar os níveis de HDL-c e pode melhorar o sistema cardiovascular parâmetros como cálcio da artéria coronária, microcirculação, tecido adiposo epicárdico e periaórtico tecidual, hiperemia reativa pós-oclusiva, placa de baixa atenuação, espessura médio-intimal da carótida; e espessura médio-intimal da carótida. Por essas razões, o alho pode ser considerado na prevenção e tratamento de fatores de risco de DCV.
Alho: uma revisão sistemática dos efeitos sobre doenças cardiovasculares
Artigo científico válido como TCC
Keywords: Alho; Doenças cardiovasculares; Saúde; Produção Alimentícia